Association between polychlorinated biphenyls and hypertension risk: a systematic review and meta-analysis - Hamzavi, Seyedeh Fatemeh; Elahi Vahed, Iman; Samadi Shams, Ali; Nozari, Fateme; Gamzeh Latava, Baroukh; Mardukhi, Saman; Sabaghi, Behnoosh; Hosseini, Zakieh Sadat; Masoumi Shahr-e Babak, Zohre; Ahrari, Sahar; Keshavarzian, Ali; Rahmanian, Mohammad (Frontiers in Cardiovascular Medicine, 2025)
Background and AimHypertension (HTN) is a widespread global health challenge, and its increasing prevalence is attributed to individual and environmental risk factors. Persistent organic pollutants (POPs), especially polychlorinated biphenyls (PCBs), contribute to cardiovascular risk by accumulating in fatty tissues, which leads to oxidative stress and vascular inflammation. This review and meta-analysis aimed to investigate the association between PCB exposure and hypertension.MethodsAdhering to the PRISMA 2020 guidelines, data sources such as PubMed, Scopus, Web of Science, and Google Scholar were systematically searched up to July 2024 to find observational studies on the link between PCBs and hypertension risk. Studies were reviewed and chosen according to established inclusion and exclusion criteria, focusing on observational studies examining PCB exposure and hypertension risk. Independent reviewers conducted data extraction, and the quality of studies was evaluated using the JBI critical appraisal tool. A meta-analysis with a random-effects model was conducted to determine combined odds ratios (ORs) for hypertension linked to total PCB exposure and specific PCB types.ResultsOf the 494 records identified, 21 studies met the inclusion criteria, comprising 5 cohort studies, 15 cross-sectional studies, and one case-control study, totaling 51,514 participants. Exposure to total PCBs correlated with an elevated risk of hypertension (OR = 1.78, 95% CI: 1.30–2.44). Dioxin-like PCBs were also associated with a heightened risk (OR = 1.54, 95% CI: 1.24–1.90), while non-dioxin-like PCBs were not significantly linked (OR = 1.16, 95% CI: 0.81–1.66). Among individual congeners, PCB-74, PCB-118, PCB-105, and PCB-153 were significantly related to higher hypertension risk.ConclusionThese findings indicate a positive correlation between PCB exposure and hypertension, particularly with dioxin-like PCBs and certain PCB congeners. Additional research is necessary to clarify the mechanisms involved and to promote measures for reducing PCB exposure, particularly in high-risk populations.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024595223, PROSPERO (CRD42024595223).